2018
DOI: 10.1115/1.4039956
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Evaluation of a UHMWPE Hybrid Nanocomposite Coating Reinforced With Nanoclay and Carbon Nanotubes Under Dry Conditions

Abstract: A novel hybrid polymer nanocomposite coating of ultrahigh molecular weight polyethylene (UHMWPE) reinforced with nanoclay (C15A) and carbon nanotubes (CNTs) has been developed to protect metallic mating surfaces in tribological applications. The hybrid nanocomposite coatings were deposited on aluminum substrates using an electrostatic spraying technique. Ball-on-disk wear tests using a 440C stainless steel ball as the counterface were conducted on the coatings under dry conditions to determine the optimum amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…Just like in the case of bulk UHMWPE, it is essential to improve the load bearing capacity of the UHMWPE coating for better performance. One of the strategies used by researchers is to develop UHMWPE nanocomposite and hybrid nanocomposite coatings reinforced with various nanofillers, such as carbon nanotubes (CNTs) [27,28], graphene [29], nanoclay [30], and nanoclay/CNTs [31]. Azam et al [30] reinforced UHMWPE with different wt % of nanoclay and found that 1.5 wt % nanoclay-reinforced UHMWPE coating did not fail until 100,000 cycles at a normal load of 9 N and a linear speed of 0.1 m/s.…”
Section: Methodsmentioning
confidence: 99%
“…Just like in the case of bulk UHMWPE, it is essential to improve the load bearing capacity of the UHMWPE coating for better performance. One of the strategies used by researchers is to develop UHMWPE nanocomposite and hybrid nanocomposite coatings reinforced with various nanofillers, such as carbon nanotubes (CNTs) [27,28], graphene [29], nanoclay [30], and nanoclay/CNTs [31]. Azam et al [30] reinforced UHMWPE with different wt % of nanoclay and found that 1.5 wt % nanoclay-reinforced UHMWPE coating did not fail until 100,000 cycles at a normal load of 9 N and a linear speed of 0.1 m/s.…”
Section: Methodsmentioning
confidence: 99%
“…Azam et al [ 75 ] conducted one such study whereby they developed a novel hybrid nanocomposite coating of UHMWPE reinforced with two nanofillers, namely: nanoclay (C15A) and carbon nanotubes (CNTs). They selected nanoclay based upon its excellent mechanical properties and barrier properties.…”
Section: Uhmwpe Coatings For Different Applicationsmentioning
confidence: 99%
“…Raman spectroscopy : Researchers have also used Raman spectroscopy to ascertain the dispersion of the nanofillers and also to evaluate their interfacial interaction with the UHMWPE matrix. Umar et al [ 75 , 76 ], used Raman spectroscopy to evaluate the interaction of CNTs with the UHMWPE matrix, based upon the shifting of the peaks corresponding to the G-band to higher wave numbers. The shifting of the G band towards higher frequencies is attributed to the disentanglement of the CNTs in the UHMWPE matrix as a result of polymer penetration into the CNT bundles, resulting in a good load transfer.…”
Section: Uhmwpe Coatings For Different Applicationsmentioning
confidence: 99%
See 2 more Smart Citations